Fun Learning by Applying Competition and Cooperation Strategies Through Mathematical Games - Sundari, Sundari; Hertuti, Anis (Program Magister Teknologi Pendidikan Universitas Jambi, 2022)
The aim of this research is to create a joyful learning environment through a competitive and cooperative activities by using mathematics games. The subject of this research is elementary school the fourth grade students. The research conducted in the Edu-Fun Learning Centre in Talang bakung, Jambi. This is Classroom Action Research (CAR). The instrument used is observation and video recording of learning activities. The qualitative data analyzed by employing the Miles and Huberman (1994).The research was conduct for three cycles. The result showed that 1) the use of games in learning mathematics created a fun and interestingly learning, 2) grouping students randomly based on academic ability to effectively train students mutually learn and work together to get better grades, 3) competition in learning activities trained students to be sportive, learning to posed ideas, and confident to answer teacher’s questions, 4) students response in learning activities affects students achievement, 5) competitiveness does not affect students learning achievement directly but able to make students actively involved in learning activity, 6) the cognitive, affective and physicomotoric achievement based on students response, the classroom teaching process, competitive character, and students active involvement in learning activities.